Brief gatekeeper training for suicide prevention in an ethnic minority population: a controlled intervention. Issue 1 (December 2016) - Teo, Alan; Andrea, Sarah; Sakakibara, Rae; Motohara, Satoko; Matthieu, Monica; Fetters, Michael
Abstract Background Suicide is a critical public health problem around the globe. Asian populations are characterized by elevated suicide rates and a tendency to seek social support from family and friends over mental health professionals. Gatekeeper training programs have been developed to train frontline individuals in behaviors that assist at-risk individuals in obtaining mental health treatment. The purpose of this study is to assess the efficacy of a brief, multi-component gatekeeper intervention in promoting suicide prevention in a high-risk Asian community in the United States. Methods We adapted an evidence-based gatekeeper training into a two-hour, multi-modal and interactive event for Japanese-Americans and related stakeholders. Then we evaluated the intervention compared to an attention control using mixed methods. Results A sample of 106 community members participated in the study. Intervention participants (n = 85) showed significant increases in all three types of intended gatekeeper behavior, all four measures of self-efficacy, and both measures of social norms relevant to suicide prevention, while the control group (n = 48) showed no significant improvements. Additional results showed significantly higher satisfaction and no adverse experiences associated with the gatekeeper training. The separate collection of qualitative data, and integration with the quantitative survey constructs confirmed and expanded understanding about the benefits of the intervention. Conclusions A brief, multi-modal gatekeeper training is efficacious in promoting positive gatekeeper behaviors and self-efficacy for suicide prevention in an at-risk ethnic minority population of Japanese Americans.